The DOF Transcription Factor SlDOF10 Regulates Vascular Tissue Formation During Ovary Development in Tomato - Rojas-Gracia, Pilar; Roque, Edelín; Medina, Mónica; López-Martín, María Jesús; Cañas, Luis A.; Beltrán, José Pío; Gómez-Mena, Concepción (Frontiers in Plant Science, 2019)
The formation of fruits is an important step in the life cycle of flowering plants. The process of fruit development is highly regulated and involves the interaction of a complex regulatory network of genes in both space and time. To identify regulatory genes involved in fruit initiation in tomato we analyzed the transcriptomic profile of ovaries from the parthenocarpic PsEND1:barnase transgenic line. This line was generated using the cytotoxic gene barnase targeted to the anthers with the PsEND1 anther-specific promoter from pea. Among the differentially expressed genes we identified SlDOF10, a gene coding a DNA-binding with one finger (DOF) transcription factor which is activated in unpollinated ovaries of the parthenocarpic plants. SlDOF10 is preferentially expressed in the vasculature of the cotyledons and young leaves and in the root tip. During floral development, expression is visible in the vascular tissue of the sepals, the flower pedicel and in the ovary connecting the placenta with the developing ovules. The induction of the gene was observed in response to exogenous gibberellins and auxins treatments. To evaluate the gene function during reproductive development, we have generated SlDOF10 overexpressing and silencing stable transgenic lines. In particular, down-regulation of SlDOF10 activity led to a decrease in the area occupied by individual vascular bundles in the flower pedicel. Associated with this phenotype we observed induction of parthenocarpic fruit set. In summary, expression and functional analyses revealed a role for SlDOF10 gene in the development of the vascular tissue specifically during reproductive development highlighting the importance of this tissue in the process of fruit set.